BIROKRASI TRADISIONAL DI JAWA DALAM PERSPEKTIF SEJARAH - Setianto, Yudi (Paramita: Historical Studies Journal, 2010)
Historically, the bureaucracies that emerged and developed today have characteristics inheriting the traditional value system which grows in the kingdoms of the past and mixed with colonial-style bureaucracy and modern ideas.ÃÂ Javanese traditional bureaucracy is the most influential among the other regions because of Java as the center of various activities of socio-political and socio-economic activities (Hindu-Buddhist), the Islamic period, the colonial period and the period of independence.ÃÂ From varius influence mentioned aboce in cultural perspective, it seems that the aspect of feudal-aristochratic values tend to give more colour on Indonesian government buerucracy. It is due to the fact that bureaucracy has been rooted in the socio-political life in Indonesia or Java.ÃÂ Traditional bureaucracy is an interesting thing because the bureaucracy is very complex when viewed from the historical angle. Keywords: Bureaucracy, traditional, Java ÃÂ  ÃÂ  Secara historis, birokrasi yang muncul dan berkembang sekarang ini mempunyai ciri khas mewarisi sistem nilai tradisional yang tumbuh di masa kerajaan-kerajaan masa lampau dan bercampur dengan birokrasi gaya kolonial serta ide-ide modern. Birokrasi tradisional Jawa paling berpengaruh di antara daerah lain karena Jawa sebagai pusat berbagai aktivitas sosio-politik dan sosio-ekonomi masa kuno (Hindu-Budha), masa Islam, masa kolonial dan masa kemerdekaan. Dari berbagai pengaruh di atas-dalam perspektif kultural-nampaknya unsur nilai-nilai tradisional yang feodal-aristokratis cenderung lebih besar mewarnai sosok birokrasi pemerintah Indonesia disebabkan birokrasi tersebut telah mengakar dalam kehidupan sosio-politik di Indonesa atau Jawa. Birokrasi tradisional sebagi hal yang menarik karena birokrasi tersebut bersifat sangat komplek jika dilihat dari sudut historisnya. ÃÂ  Kata kunci: birokrasi, tradisional, Jawa ÃÂ